Correlation of microcrack fracture size with fatigue cycling on non-crimp fabric/RTM6 composite in the uniaxial fatigue test - Shiino, M. Y. [UNESP]; De Camargo, L. M. [UNESP]; Cioffi, M. O. H. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Ortiz, E. C.; Rezende, M. C. (Elsevier B.V., 2012)
Quantitative fractographic studies have become an important field to understand the fracture process. Future trends pointed out quantitative fractographic analysis as an important tool for a better comprehension of the damage and currently it had been focused on studies about geometric attributes of the fracture topographic surface and microstructure features. This research aimed a quantitative analysis of the cusp aspects generated in an axial fatigue test by carrying out fractographic measurements in order to know their influence on the fatigue test parameters, e.g. stress level, number of cycles, frequency, and stress ratio. Fatigue tests in tension-tension mode were undertaken in different stress levels, consequently leading to different number of cycles. Quasi-isotropic laminates were fatigue tested until the fracture, which was observed in SEM, and the hackle patterns were measured in the public domain program called Image J. The response of the laminate obeyed a cusp size pattern according to a number of cycles until the fracture was reached. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Laminate; Fatigue; Fractography